Maintaining viability of rubber shelled seed for storage of 16 days period by polyethylene glycol 6000 treatments - . Charloq; Zulkifli Lubis; Tumpal H. Siregar; Sengly B. Damanik; J. Elisa; M. Husni (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Rubber seeds have no dormancy, germinate rapidly and fungal growth is the limiting factor influencing storage period of seed viability. Solution of Polyethylene glycol 6000 (PEG 6000) have osmotic potential and osmotic adjustment that is used as a coating material is expected to be a preservative during storage. The purpose of this study was to test the effect of polyethylene glycol 6000 in inducing secondary dormancy by reducing the seeds germination and fungus growth to maintain the seed viability in storage period and to test seed viability and vigor after storage period. First stage of the study was using nonfactorial completely randomized design with four levels of polyethylene glycol with four replications, namely:PEG 6000 (w / v): 0%, 15%, 30%, 45%; The second step, was germination phase in germination tub after the storage period. The first study showed that concentration of 15% PEG 6000 to 45% were able to induced secondary dormancy by delaying seed germination from 0.67% to 0.33%, that significantly different from the 0% PEG 6000 (17.67%) that was able to reduced fungal seed from 16.33 to 26.33% andwas not significantly different in each treatment. The second study showed that PEG 6000 can maintain viability and vigor of seeds with seed germination above 97%, seedlings height 22.40 cm and number of leaves was 7.16. PEG 30% is the best concentration to increase the shelf life period of rubber seed andmaintained morphological characteristics after storage period. The higher the concentration of PEG 6000 the higher were the seed viability during shelf. The morphology and growth of the seedlings, had the same adaptability to the tub germination in planting medium.